Ideal Mariano e docência: a identidade feminina da Proposta Educativa Marista - Nunes, Iran de Maria Leitão (2006)
In the teaching history course it s found the female teacher entering, reflecting significantly in the continuous process of her identity redefinitions and reconstruction. This entering brings, even in a silent and not explicit way, the confluence of gender identity to professional identity, in which are present the relations of the proper to female. In the mastership case, these relations are found imbricated in the teaching identity construction and in the translation of this profession as female, based in Virgin Mary, through Mariano ideal diffused by the catholic church. Therefore there is a lanck in educational historiography towards the register of female teachers presence, mainly in male religious institute, the reason of this study, in which we seek to investigate: how to explain that a female identity can give support to a highly male educational project? What relations can we establish between this female identity and the entering of female teachers in Maristas Province Schools of North Brazil? We performed a bibliographic research in Maristas Schools Libraries, of Marista historial, in Recife, of Pontificia Universidade Católica do Paraná (Catholic University), in Curitiba-PR. We searched for support in studies about pedagogy history, of Marista Institute, Catholic Church, Brasilian Education and of Women; Mariologic studies, the referring to Marista Educational Proposal, to feminization and to teaching identity; and feminist theology productions. The empirical research included 10 schools from referred province and Marista Schools from Lisbon Portugal. Through semi-estructured interviews, we interviewed pioneer female teachers, Marista former Brothers and Brothers from those schools, due to their presence and action within the study period and for the concern to save their memories about the theme. The study reveals the particularities of Mariano ideal as female model and teaching, and her presence in Marista Educational Proposal. This study, in a historical approach, aims to contribute to give visibility to the woman in history and teaching construction in Brazil, mainly in religious institutions from male origin